Gambaran Dukungan Keluarga Tentang Perawatan Kehamilan Pada Ibu Di Wilayah Kerja Puskesmas Sedayu II Bantul Tahun 2017 - Dwi Ismaryati; Bondan Palestin; Ida Mardalena (Poltekkes Kemenkes Yogyakarta, 2017)
Pregnancy care is one of step to decrease the maternal mortality rate. The maternal mortality cases in Bantul in 2015 there are 11 cases and “K4” coverage decreased from 92,05% to 90,98%.The family support has an important role in influcing the behavior of mother doing pregnancy care.The family can motivate, give a sense of comfort, both physical and psychological needs for pregnant mother. The purpose of this research is to know the description of family support about pregnancy care to mother at work area of Sedayu II Primary Health Center in 2017. The design of this research is descriptive using survey methods. The sample in this research are 48 respondents. The sampling technique used purposive sampling and data collection using questionnaire. Family support about pregnancy care showed that the instrumental support of family in good category (56,25%), informational support in enough category (54,17%), appraisal support in good category (54,17%), and emotional support in good category (70,83%). The conclusion of research shown that family support about pregnancy care to mother at working area of Sedayu II Primary Health Center in 2017 in good category.